You are on page 1of 19

# 3

## Manipulation of Simple Polynomials

Level 1 Questions
(P01C03L03Q047)
Find the value of the expression 413 411 4 without using a calculator.
Solution
413 411 4 = 413 11+1
= 43
=64

(P01C03L03Q048)
Find the value of the expression 38 26 34 311 25 without using a calculator.
Solution
38 2 6 34 311 25 = 38 34 311 2 6 25
= 38 +4 11 26 5
= 31 21
=6

(P01C03L03Q049)
Simplify 6 y 4 y 3 2 y 5 .
Solution
6 y 4 y3 2 y5 =

6 4 +3 5
y
2

=3y2

## Question Bank Update 1A

(P01C03L03Q050)
Simplify

2r r 5
16r 2

Solution
2r r 5
16r 2

r1+5 2
8

r4
8

(P01C03L03Q051)
Simplify m3

2m 9
6m 6

Solution
m3

2m9

1
= m3+9 6
3
6m
6

m6
3

(P01C03L03Q052)
Simplify y 5 (

y3
).
2

Solution
y 5 (

y3
2
) = y 5 ( 3 )
2
y
= 2 y 5 3
=2 y 2

(P01C03L03Q053)
Write down the coefficients and the degree of the following monomials.
(a) 2xy
(b)

x3
5

Solution
(a) The coefficient of xy in 2xy = 2
The degree of 2xy = exponent of x + exponent of y
2

## Manipulation of Simple Polynomials

=1+1
=2
3

x
1
(b) The coefficient of x 3 in 5 = 5

The degree of

x3
=3
5

(P01C03L03Q054)
Complete the following table.
Polynomial

x3 +

Number
of terms

Coefficient of
x3

x2

Constant
term

Degree of
polynomial

Degree of
polynomial

x2
+ 3 x 10
2

8x 2 + x 2

Solution
Polynomial

x3 +

x2
+ 3 x 10
2

8x 2 + x 2

Number
of terms

Coefficient of
x3

x2

Constant
term

1
2

10

(P01C03L03Q055)
Simplify the following polynomials.
(a) 6 y + y 2 5 y 2 + 3 2 y
(b)

m
5m
x+
+ 9x
3
3

## Question Bank Update 1A

Solution
(a)

6 y + y 2 5 y 2 +3 2 y
= y 2 5 y 2 +6 y 2 y +3
= 4 y 2 + 4 y +3

(b)

m
5m
x +
+9x
3
3
m 5m
= +
x +9x
3
3
= 2m + 8 x

(P01C03L03Q056)
For the polynomial

t2
t4
+ 1 + 6t ,
5
9

## (a) write down the degree of the polynomial,

(b) arrange the terms in both descending powers and ascending powers of t respectively.
Solution
(a) The degree of the polynomial

t2
t4
+ 1 + 6t is 4.
5
9

t4 t2
+ 6t + 1
9
5

## Arranged in ascending powers of t: 1 + 6t

t2 t4

5
9

(P01C03L03Q057)
Find the value of the polynomial u 2 + 2u 1 in each of the following cases.
(a) u = 2
(b) u = 1
Solution
(a)

(b)

## When u = 2, the value of the polynomial = (2) 2 +2( 2) 1

= 4 +4 1
=7
When u = 1, the value of the polynomial =( 1) 2 +2( 1) 1
=1 2 1
=2

(P01C03L03Q058)
4

## Manipulation of Simple Polynomials

x
in each of the following cases.
9

(a) x = 1
(b) x = 3
Solution
When x =1, the value of the polynomial = (1)3 +

(a)

= 1 +
=

1
9

1
9

8
9

## When x = 3, the value of the polynomial = (3)3 +

(b)

= 27
= 26

(P01C03L03Q059)
Simplify ( a + 2b c ) + (b + 2c a ) .
Solution
(a + 2b c) + (b + 2c a ) = a a + 2b + b c + 2c
= 3b + c

(P01C03L03Q060)
Simplify ( 2 x + y 4 z ) + ( z y x ) .
Solution
(2 x + y 4 z ) + ( z y x) = 2 x x + y y 4 z + z
= x 3z

2
3

1
3

3
9

## Question Bank Update 1A

(P01C03L03Q061)
Expand 2(6 x y ) .
Solution
2(6 x y ) =12 x +2 y

(P01C03L03Q062)
Expand ( x +1)(3x 2) .
Solution
( x +1)(3 x 2) =( x +1)(3 x ) ( x +1)( 2)
=(3 x 2 +3 x ) (2 x +2)
=3 x 2 +3 x 2 x 2
=3 x 2 + x 2

(P01C03L03Q063)
Expand ( y 2) 2 .
Solution
( y 2) 2 = ( y 2)( y 2)
= ( y 2)( y ) ( y 2)(2)
= ( y 2 2 y ) ( 2 y 4)
= y2 2 y 2 y + 4
= y2 4 y + 4

## Manipulation of Simple Polynomials

Level 2 Questions
(P01C03L04Q038)
Simplify

23s +1
23s 1

Solution
23s +1
23s 1

= 2 (3 s +1) (3s 1)
= 23 s +13s +1
= 22
=4

(P01C03L04Q039)
Simplify 6 x12

2 x3
(x 5 ) .
9

Solution
6 x12

2 x3
9
(x 5 ) = 6 x12 3 (x 5 )
9
2x
6 9 12 35
=
x
2
= 27 x 4

(P01C03L04Q040)
Simplify 27 p 4 q 7

q2
p2 .
9p

Solution
27 p 4 q 7

q2
p 2 = 3 p 4 12 q 7 +2
9p
= 3 pq 9

(P01C03L04Q041)
Write down the degrees and the constant terms of the following polynomials.
(a) x 6 4 z 2 xyz + x 4 y 2 z 1
(b) 3a 2b + 2 bc 3 + c 5
Solution

## (a) The degree of the polynomial

The constant term is 1.

x 6 4 z 2 xyz + x 4 y 2 z 1

is 7.

## (b) The degree of the polynomial 3a 2b + 2 bc 3 + c 5 is 5.

The constant term is 2.
(P01C03L04Q042)
Simplify x 2 2 x + 2 x 4 + 5 x + 3 x 2 x 3 .
Solution
x 2 2 x + 2 x 4 +5 x +3 x 2 x 3
= x 4 x 3 + x 2 + 3 x 2 2 x + 5 x + 2
= x 4 x 3 + 4 x 2 +3 x + 2

(P01C03L04Q043)
Find the value of the polynomial
(a) x = 1, y = 2
(b) x = 2, y = 1

x 2 +2 xy 1

## in each of the following cases.

Solution
(a) When x = 1, y = 2,
the value of the polynomial

=12 +2(1)(2) 1
=1 +4 1
=4

(b) When x = 2, y = 1,
the value of the polynomial

=( 2) 2 +2( 2)( 1) 1
=4 +4 1
=7

## Manipulation of Simple Polynomials

(P01C03L04Q044)
Suppose there are 2 000 000 birds living in the New Territories in winter, and x 2 400 x of them
carry bird flu.
(a) Express the number of birds that do not carry bird flu in terms of x.
(b) Hence, find the number of birds that do not carry bird flu if x = 1000.
Solution
(a) Number of birds that do not carry bird flu
=2 000 000 ( x 2 400 x )
=x 2 +400 x +2 000 000

## (b) Number of birds that do not carry bird flu

= (1000) 2 +400(1000) +2 000 000
= 1 000 000 +400 000 +2 000 000
=1 400 000

(P01C03L04Q045)
Expand ( x y )(5 x 2 y ) and arrange the terms in descending powers of x.
Solution
( x y )(5 x 2 y ) =( x y )(5 x ) ( x y )(2 y )
=(5 x 2 5 xy ) ( 2 xy 2 y 2 )
=5 x 2 5 xy 2 xy +2 y 2
=5 x 2 7 xy +2 y 2

(P01C03L04Q046)
A telecommunications company gives free mobile phones to its service users. Suppose it has
360 000 1200 x users and each mobile phone costs \$(900 +1.2 x) .
(a) Find the cost of mobile phones for all the users in terms of x.
(b) Find the cost in (a) when
(i) x = 50.
(ii) x = 0.

## Question Bank Update 1A

Solution
(a) Cost of mobile phones for all the users
=\$[(360 000 1200 x ) (900 +1.2 x )]
=\$[(360 000 1200 x )(900) +(360 000 1200 x )(1.2 x )]
=\$[(324 000 000 1 080 000 x ) +( 432 000 x 1440 x 2 )]
=\$( 1440 x 2 648 000 x +324 000 000)

(b) (i)

When x = 50,
cost =\$[1440 (50) 2 648 000 50 +324 000 000]
=\$288 000 000

(ii) When x = 0,
cost =\$[ 1440 (0) 2 648 000 0 +324 000 000]
=\$324 000 000

10

## Manipulation of Simple Polynomials

Level 2+ Questions
(P01C03L05Q009)
(a) Simplify (10 x + y ) 2 and arrange the terms in descending powers of x.
(b) Hence, show that (10 x +5) 2 =100 x( x +1) + 25 .
(c) Using the result of (b), find the value of the following without using a calculator.
(i) 15 15
(ii) 9595
Solution
(a)

## (10 x + y ) 2 = (10 x + y )(10 x + y )

= (10 x + y )(10 x) + (10 x + y )( y )
= 100 x 2 + 10 xy + 10 xy + y 2
= 100 x 2 + 20 xy + y 2

2
2
2
(b) (10 x + 5) =100 x + 20 x 5 + 5

=100 x 2 +100 x + 25

(c) (i)

## (10 x +5) 2 =100 x( x +1) + 25

When x = 1, we have
15 15 =100 1 (1 +1) +25
=100 1 2 +25
= 200 +25
= 225

## (ii) When x = 9, we have

95 95 =100 9 (9 +1) + 25
=100 9 10 + 25
= 9000 + 25
= 9025

11

## Question Bank Update 1A

(P01C03L05Q010)
(a) Expand ( x 2 + x + a b)( x 2 + b) + c + b(b a) and arrange the terms in descending powers of x.
(b) Hence, represent x 4 + x 3 + 5 x 2 + x + 10 in the form of ( x 2 + x + m)( x 2 + n) + k , where m, n
and k are integers.
Solution
( x 2 + x + a b)( x 2 +b) + c +b(b a )

(a)

## = ( x 2 + x + a b)( x 2 ) + ( x 2 + x + a b)(b) + c +b(b a )

= x 4 + x 3 + ax 2 bx 2 +bx 2 +bx + ab b 2 + c +b 2 ab
= x 4 + x 3 + ax 2 +bx + c

x 4 + x 3 +5 x 2 + x +10

(b)

## = ( x 4 + x +5 1)( x 2 +1) +10 +(1)(1 5)

= ( x 4 + x +4)( x 2 +1) +10 4
= ( x 4 + x +4)( x 2 +1) +6

12

## Multiple Choice Questions

(P01C03L06Q032)
Simplify ( 2 y 2 )(3 y 4 ) .
A. 6 y 6
B. 6 y 8
C. 6 y16
D. 6( y 2 + y 4 )
Solution
A
( 2 y 2 )(3 y 4 ) =2(3) y 2 +4
=6 y 6

(P01C03L06Q033)
Simplify

3a 4a 8
6a 4

A.

2a 2

B.

1 4
a
2

C.
D.

2a 4
2a 5

Solution
D
3a 4a 8
3 4 1+8 4
=
a
6
6a 4
= 2a 5

13

## Question Bank Update 1A

(P01C03L06Q034)
Simplify 28 x 5 y 3 4 x x 2 y .
A. 7 xy
B. 7 x 2 y 2
C. 7 x 6 y 4
D.

7x
y2

Solution
B
28 x 5 y 3 4 x x 2 y =7 x 5 12 y 3 1
=7 x 2 y 2

(P01C03L06Q035)
Find the constant term in
A. 5
B. 5
C. 3
D. 3

(9 x 3 8 x + 4) (2 x + 7 x 2 )

Solution
C
(9 x 3 8 x + 4) ( 2 x + 7 x 2 )
= 9 x 3 8 x + 4 2 x 7 + x 2
= 9 x 3 + x 2 8 x 2 x + 4 7
= 9 x 3 + x 2 10 x 3

## The constant term is 3.

14

after simplification.

(P01C03L06Q036)
The coefficient of x 3 in the monomial

x3
is
2

1
.
2

A.

B.

1
.
2

C.
D.

2.
2.

Solution
A
(P01C03L06Q037)
The degree of the monomial abc 2 d 2 is
A. 2.
B. 2.
C. 6.
D. 6.
Solution
C
Degree of the monomial
= exponent of a + exponent of b + exponent of c + exponent of d
=1 +1 +2 +2
=6

(P01C03L06Q038)
The degree of the polynomial
A. 1.
B. 3.
C. 4.
D. 5.

8 y 4 5 x 3 y 2 +12 x

is

15

## Question Bank Update 1A

Solution
D
Degree of the polynomial
= degree of the term 5 x 3 y 2
= exponent of x + exponent of y
=3+2
=5
(P01C03L06Q039)
Which of the following polynomials is arranged in ascending powers of x?
A. x + 8
B. 2 + x 2
C. x 4 + x 3 10 x + 3
D. x +1 + x 2
Solution
B
(P01C03L06Q040)
Find the value of the polynomial 5 x 2 x + 2 when x = 1 .
A. 2
B. 5
C. 6
D. 8
Solution
D
When

x = 1

## , the value of the polynomial

=5( 1) 2 ( 1) +2
=5 +1 +2
=8

16

(P01C03L06Q041)
Simplify (2a ab + 8b) 2[4ab (3b 9a)] .
A. 7 a 9ab +11b
B. 20a 9ab +14b
C. 16a 9ab +14b
D. 20a 9ab + 2b
Solution
C
( 2a ab +8b) 2[4ab (3b 9a )]
= 2a ab +8b 2( 4ab 3b +9a )
= 2a ab +8b 8ab +6b 18a
= 16a 9ab +14b

(P01C03L06Q042)
Simplify (5 x 3 + x 2 + 6 x + 2) + (4 x 2 + 3 x 1) .
A. 4 x 2 +13 x +1
B. 4 x 3 + 4 x 2 + 9 x +1
C. 5 x 3 + 5 x 2 + 9 x 1
D. 5 x 3 + 5 x 2 + 9 x +1
Solution
D
( 5 x 3 + x 2 + 6 x + 2) + ( 4 x 2 +3 x 1)
= 5 x 3 + x 2 + 4 x 2 + 6 x +3 x + 2 1
= 5 x 3 +5 x 2 +9 x +1

(P01C03L06Q043)
Find the coefficient of x 2 in (2 x +1)(5 7 x) after simplification.
A. 5
B. 5
C. 14
D. 14

17

## Question Bank Update 1A

Solution
C
( 2 x +1)(5 7 x ) = ( 2 x +1)(5) (2 x +1)(7 x)
=10 x +5 (14 x 2 + 7 x )
= 14 x 2 +3 x +5

## The coefficient of x 2 is 14.

(P01C03L06Q044)
Expand ( x 2)(3 x +1) .
A. 3x 2 5 x 2
B. 3 x 2 + 4 x + 2
C. 3x 2 + 5 x 3
D. 3x 2 7 x 2
Solution
A
( x 2)(3 x +1) =( x 2)(3 x ) +( x 2)(1)
=3 x 2 6 x + x 2
=3 x 2 5 x 2

(P01C03L06Q045)
Find the value of the product of 4 x 3 x 2 + 5 x 2 and 6 x 2 + x +1 when x = 0 .
A. 4
B. 2
C. 1
D. 4
Solution
B
When x = 0 ,
4 x 3 x 2 + 5 x 2 = 2
6 x 2 + x +1 =1
(4 x 3 x 2 +5 x 2)(6 x 2 + x +1) = (2)(1)
= 2

(P01C03L06Q046)
Expand 2( x +2 y )( y 2 xy ) and arrange the terms in ascending powers of x.

18

A.
B.
C.
D.

2 x 2 y +2 xy 2 4 y 3
4 y 3 + 2 xy 2 + 2 x 2 y
4 y 3 xy 2 x 2 y
x 2 y xy 2 4 y 3

Solution
B
2( x +2 y )( y 2 xy ) =2[( x +2 y )( y 2 ) ( x +2 y )( xy )]
=2[ xy 2 +2 y 3 ( x 2 y +2 xy 2 )]
=2( xy 2 +2 y 3 x 2 y 2 xy 2 )
=2( 2 y 3 xy 2 x 2 y )
=4 y 3 +2 xy 2 +2 x 2 y

19